Coffee and its Biologically Active Components: Is There a Connection to Breast, Endometrial, and Ovarian Cancer? - a Review - Anna Maria Witkowska; Iwona Mirończuk-Chodakowska; Katarzyna Maria Terlikowska; Kamila Kulesza; Małgorzata Elżbieta Zujko (Polish Journal of Food and Nutrition Sciences)
Coffee is an important dietary source of biologically active components, not to mention caffeine, phenolic acids, and diterpenes. It has been suggested that selected coffee secondary metabolites may beneficially modulate several mechanisms of anti-cancer protection. This literature review was intended to present current knowledge related to coffee and its components and hormone-dependent female cancers, such as breast, endometrial and ovarian cancer, and to identify gaps in research that may be exploited in the future. The search for studies was conducted through electronic databases. Publications on coffee composition, coffee preparation and brewing methods, in vitro and in vivo experiments with the use of substances naturally present in coffee, observational studies, and meta-analyses were collected. In population studies, the greatest attention has been paid to the anticancer effect of caffeinated coffee and/or caffeine. In general, most studies and meta-analyses indicated that there was no clear correlation between coffee and breast cancer or ovarian cancer. Some subgroups of women may benefit from coffee consumption. This is the case for post-menopausal women with regard to the risk of breast cancer and obese women with regard to the risk of endometrial cancer. This paper identifies a number of issues for future research, related to a better understanding of the anti-cancer mechanisms of coffee compounds and further research that would focus on specific target groups, taking into account both the different methods of coffee preparation and lifestyle factors that may influence the results.